2021
DOI: 10.1002/cnma.202100125
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphonium‐Derived Bright Green Fluorescent Carbon Dots for Mitochondrial Targeting and Rapid Selective Detection of Tetracycline

Abstract: Although various fluorescent‐based nanoparticles are treated as cellular imaging probes, approaching the construction of a biocompatible subcellular imaging probe is challenging. At the same time, the recognition of wasted pharmaceutical drugs by some fluorescent nanoprobes is important and urgently required. We report a “structural memory” concept for simple one‐pot synthesis of bright green fluorescent (quantum yield of up to 61%) carbon dots (C‐dots) from triphenylphosphonium (TPP) as a carbon precursor tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…To further clarify this deduction, UV/vis absorption spectra, FT-IR, and zeta-potential analysis were implemented. Absorption spectra of N/P CDs were notably affected and changed after the addition of Fe 3+ ( Figure 4B ), which was attributable to the strong chemical interaction between Fe 3+ and N/P CDs followed by stable metal complex formation ( Rajendran et al, 2021 ). Absorption peaks of N/P CDs shifted to their former position again with the addition of F − .…”
Section: Resultsmentioning
confidence: 99%
“…To further clarify this deduction, UV/vis absorption spectra, FT-IR, and zeta-potential analysis were implemented. Absorption spectra of N/P CDs were notably affected and changed after the addition of Fe 3+ ( Figure 4B ), which was attributable to the strong chemical interaction between Fe 3+ and N/P CDs followed by stable metal complex formation ( Rajendran et al, 2021 ). Absorption peaks of N/P CDs shifted to their former position again with the addition of F − .…”
Section: Resultsmentioning
confidence: 99%
“…This is ascribed to the relatively uniform size and surfacepassivated C-dots which supply a narrow distribution of surface energy states. 43,44 The TEM image in Figure 1C reveals the formation of small-sized nanoparticles of less than 10 nm. The crystalline graphitic organization of the C-dots with an interplanar d spacing of 0.215 nm in the HRTEM image (inset) is representative of [110] graphitic planes.…”
Section: Resultsmentioning
confidence: 99%
“…These are assigned to sp 2 and sp 3 carbons, respectively. 46 The N 1s spectrum has a peak at 398.6 eV as shown in Figure 2B, corresponding to C−N and/or CN groups, 44 whereas the deconvoluted O 1s peaks at 529.7 and 531.2 eV are assigned to CO and C−OH groups, respectively, in Figure 2C. 46 The presence of the elements was also confirmed by elemental analysis, the weight percentage of C:H:N was 65:1:8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Triphenylphosphonium (TPP) moiety, a substance commonly used to target mitochondria, does not have biological activity but interacts with phospholipids components. [9][10][11] Interestingly, certain TPP derivatives have a negative effect on mitochondrial membrane potential and respiratory chain activity. 12 For example, Trnka et al reported that TPP-alkyl derivatives induce increased proton leak and decreased activity of electron chain complexes, causing mitochondrial dysfunction.…”
mentioning
confidence: 99%